A Rapid Intraoperative Parathyroid Hormone Assay Based on the Immune Colloidal Gold Technique for Parathyroid Identification in Thyroid Surgery - Xia, Wenfei; Zhang, Jinjun; Shen, Wenzhuang; Zhu, Zhi; Yang, Zhifang; Li, Xingrui (Frontiers in Endocrinology, 2021)
Objective: A novel immunochromatographic test strip method was developed to detect tissue parathyroid hormone (PTH) using the immune colloidal gold technique (ICGT). The accuracy and application value of this method for intraoperative parathyroid identification were evaluated. Methods: Serum samples were collected to measure PTH by both ICGT and electrochemiluminescence immunoassay (ECLIA). Patients who underwent unilateral and total thyroidectomy were enrolled to evaluate the feasibility and clinical efficacy of rapid intraoperative identification of parathyroid glands via PTH determination using ICGT. Two sample preparation methods, fine needle aspiration (FNA) and tissue block homogenate (TBH), were used for PTH-ICGT analysis. Results: Bablok analysis showed a linear relationship between the serum PTH measurements obtained by ICGT and ECLIA. Non-parathyroid tissues had much lower PTH concentrations (14.8±2.1 pg/ml, n=97) detected by ICGT, compared to the parathyroid gland tissues (955.3±16.1 pg/ml, n=79; P<0.0001), With biopsy results as the standard, ICGT showed higher diagnosis rates as compared with direct visual inspection, for identifying both parathyroid glands (97.4% vs. 78.2%) and non-parathyroid tissues (100% vs. 68.9%). The cut-off values for parathyroid identification by FNA and TBH methods were 63.99 pg/ml and 136.30 pg/ml, respectively. The detection time was 2 minutes by TBH method for in vitro tissue detection and 6 minutes by FNA method for in situ tissue detection, both of which were faster than traditional intraoperative cryopathological examination (usually >30 minutes). Intraoperative application of ICGT method was associated with higher postoperative serum calcium and blood PTH levels at 1 and 3 months as well as a lower incidence of postoperative transient hypocalcemia, as compared with direct visual inspection. Conclusion: PTH-ICGT assay shows high potential as a rapid, novel alternative for intraoperative parathyroid identification.